Development of corn seedlings after a period of exposition to various water potential - Silva, W.R. da; Marcos Filho, J. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1990)
Fungicide treated and untreated corn seeds were sets to germinate under varying water availability conditions (0 to -12atm water potential). The seedlings obtained on each individual treatment were subsequently grown under ideal available water conditions. The results permitted to conclude that the occurrence of a water deficit during the on set of the germination process results in reductions on the length of the embryonic structures, particularly the epicotil. This effect attenuates with times due to the increase in growth velocity in environments where water potential is lower. Fungicid treated seeds, did not appear to be consistently vantageous in environments with water stress.